2022
DOI: 10.3145/epi.2022.ene.14
|View full text |Cite
|
Sign up to set email alerts
|

Green energy: identifying development trends in society using Twitter data mining to make strategic decisions

Abstract: This study analyzes Twitter’s contribution to green energy. More than 200,000 global tweets sent during 2020 containing the terms “green energy” OR “greenenergy” were analyzed. The tweets were captured by web scraping and processed using algorithms and techniques for the analysis of massive datasets from social networks. In particular, relationships between users (through mentions) were determined according to the Louvain multilevel algorithm to identify communities and analyze global (density and centralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
6
1
4
Order By: Relevance
“…Previous studies show that the debate in the digital sphere is positive when talking about green energy (Zarrabeitia-Bilbao et al 2022a ); however, in this case, it is observed that this is not the general tendency. In the first period, although there were negative peaks, such as the one on February 13 (Fig.…”
Section: Resultscontrasting
confidence: 56%
“…Previous studies show that the debate in the digital sphere is positive when talking about green energy (Zarrabeitia-Bilbao et al 2022a ); however, in this case, it is observed that this is not the general tendency. In the first period, although there were negative peaks, such as the one on February 13 (Fig.…”
Section: Resultscontrasting
confidence: 56%
“…Setelah itu melakukan pembersihan dapat dengan OpenRefine dan Orange Data Mining. Data diproses dan dianalisis dengan menggunakan Pajek, Gephi, Excel (Power Query), WordArt, dan Orange Data Mining (Zarrabeitia-Bilbao et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…(4) Didasarkan pada premis bahwa artificial intelligence (AI) yang dibantu media sosial dan big data adalah tools yang inovatif untuk menganalisis topik-topik penting bagi kepentingan publik (Khan & Gupta, 2023) (5) Menganalisis hubungan antar aktor dengan Louvain multilevel algorithm dan analisis secara global, yaitu density dan centralization serta matriks level aktor (centrality) (Zarrabeitia-Bilbao et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…La red sintetizada y las comunidades detectadas en los pasos anteriores fueron posteriormente procesadas con el software Gephi, una herramienta open-source desarrollada en Java y de demostrada validez para mejorar la visualización y el análisis de grandes gráficos de red (Bastian et al, 2009). A pesar de su corta vida, Gephi ya ha devenido el estándar para visualizar redes masivas (Zarrabeitia et al, 2022). Se empleó el algoritmo Force-Atlas 2 (Jacomy et al, 2014) de Gephi por su utilidad para acercar los nodos que forman parte de las mismas comunidades y alejarlos de aquellas con las que guardan menor relación algorítmica, rechazando las comunidades que no alcanzan el 1% de la modularidad intra nodo.…”
unclassified